Authority of the Mataram City Regional Supervisory Council to Examine Notaries Based on Permenkumham Number 15 of 2020 - Baiq Silvia Yustiari; Siti Hasanah; Firzhal Arzhi Jiwantara; Nurjannah Septyanun (Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the regulation and implementation of the authority of the Mataram city notary supervisory council on notary examinations based on the Minister of Law and Human Rights Regulation number 15 of 2020. Normative-empirical research with legislative, conceptual and sociological approaches in qualitative descriptive analysis, the data used are primary, secondary and literature research materials and field research. Concluded; First, the authority of the notary supervisory council in Mataram City is guidance for preventive measures and supervision of repressive actions. Second, the obstacles in carrying out notary supervision in Mataram City are; The legal factor needs to be added to the content material that regulates administrative sanctions, both in the form of verbal reprimands, written reprimands and dismissals for members and the content of the authority to determine sanctions by the Notary MPD. Meanwhile, law enforcement factors need to reschedule the schedule during the Notary examination so that all the objectives can be present so that the examination is maximized, and the role of the NTB Notary MPW to provide education and training, FGD and socialization of regulations so as to provide the same understanding in the Notary examination in Mataram City.